Heavy-heartedness biases your weight perception. Issue 5 (2nd September 2016) - Min, Bora; Choi, Incheol
ABSTRACT: Heavy-heartedness (light-heartedness), among more than two hundred metaphors related to the heart, indicates negative (positive) affects. Although these metaphors are generally understood rhetorically, this study explores whether there is any literal connection between either of these two states and one's perception of weight. Participants who recalled a heavy-heartening (vs. light-heartening) past event estimated more weight of an object (Study 1). While watching weightlifting and pole-vaulting competition clips, people in heavy-hearted (vs. light-hearted) states predicted that players' success is less likely (Study 2). However, this result was not observed while people in both states watched non-weight-related games, such as golf-putting and pool. The findings are congruous with embodied cognition theory and the role of metaphors in our life.